Outcome of planned discharge from case management: a 3 year retrospective study - Backus, Linda; Weinkove, John; Lucas, Marilyn; Jespersen, Sean (Australasian psychiatry : bulletin of the Royal Australian and New Zealand College of Psychiatrists, 2008)
Objective: To investigate the rates of relapse of mental illness in adults requiring acute intervention at a mental health service following a planned discharge process from community case management. Method: A planned approach to identifying and facilitating patient discharge was identified and incorporated into clinical team reviews. Data regarding service contacts of all discharged patients were collected at 1 year and then 3 years following planned discharge and reviewed in detail. Demographic factors and clinical variables were collected in anticipation that useful predictors for successful discharge might be identified. Results: Using a planned approach, a greater number of patients were discharged from case management to the care of a primary treating practitioner. Discharges increased from 11 in 2000 to 46 in 2001. Of the 46 patients discharged from case management, 22 patients (47.8%) had no contact with the service during the first 12 months. Twenty-four patients accessed the Service requiring no further action, but at some point nine (19.6%) required acute intervention. The remaining 15 patients (32.6%) were managed successfully either by the triage service or non-urgent referral for psychiatric consultation. During the 3 year period 10 patients (21.7%) continued to have no contact with the service. Nineteen patients (41.3%) required acute intervention; the remaining 17 (36.9%) were successfully managed through triage or via non-urgent psychiatric review requiring no further action by the Service. Of the seven patients who had been on a community treatment order during their treatment, only one had further contact with the Service. Conclusions: A planned approach to the discharge of patients from case management to the community resulted in an increased number of patient discharges. While most patients did not rapidly relapse, a number of patients did have contact with the Service and 19 (41.3%) required at least one acute intervention during the 3 year follow-up period. The findings reflect the importance of relapse prevention and management and service re-entry planning with triage services, patients, carers and other key workers. The frequency of service use and the variation of services required by patients highlight the importance of availability of a variety of adequately resourced levels of service response.